(untitled) (Proceedings of the Global Public Health Conference, 2023)
As a result of the COVID-19 pandemic economy, health, and care systems were disrupted and this affected and shaped the future of work. The pandemic augmented many trends in employee work arrangement that had a major impact on businesses and employee health and safety and one of these trends is hybrid work arrangement. Globally, employers, government officials, health organisations, unions, and professional associations struggled to stay compliant. Occupational exposure and working conditions can have an undesirable or positive effect on the safety, health, and well-being of workers. Therefore, this study aims to analyse the effect of post-COVID office hybrid work arrangement on employee health and safety: a case study of Uni4 Online Westville Durban South Africa. Taking into consideration the aim of the study the following objectives guide the study i) to understand what hybrid work arrangement is. ii) to understand how the COVID-19 pandemic has affected employee work arrangement, iii) determine the perceived challenges and opportunities in the application of hybrid work arrangement iv) make recommendations on the effective application of hybrid work arrangement at Uni4 Online Westville Durban South Africa. For this study, a secondary approach to data collection was undertaken. In this regard a total of 15 relevant articles were searched from different databases and search engines, The keywords were explored in three databases namely, Google Scholar, Ebsco-host, and Emerald. The findings from the literature showed that post-COVID hybrid work arrangements can affect workers psychologically because physical distancing through staying at home contributes to isolation and a lack of distinction between work life and home life. Furthermore, it was deduced that hybrid work arrangement creates challenges for workers because it creates fewer opportunities for career development and promotions because of weakened ties. In addition, workers in a hybrid work arrangement who were more dependent on others and generally received more feedback had fewer positive appraisals than those with more independent roles. The study recommends that both employees and managers need to develop new skills and capabilities to adjust to the new ways of working and utilising the prospects of Post COVID hybrid work. Also, firms should be concerned about sustainability implications when developing guidelines for Post COVID hybrid work, both in terms of social and ecological aspects.